Risk-on/risk-off, capital flows, leverage, and safe assets - Robert N. McCauley (Asian Development Bank Institute (ADBI), 2013)
This paper describes the international flow of funds associated with calm and volatile global equity markets. During calm periods, portfolio investment by real money and leveraged investors in advanced countries flows into emerging markets. When central banks in the receiving countries resist exchange rate appreciation and buy dollars against domestic currency, they end up investing in medium-term bonds in reserve currencies. In the process they fund themselves (or "sterilize" the expansion of local bank reserves) by issuing safe assets in domestic currency to domestic investors. Thus, calm periods, marked by leveraged investing in emerging markets, lead to an asymmetric asset swap (risky emerging market assets against safe reserve currency assets) and leveraging up by emerging market central banks. In declining and volatile global equity markets, these flows reverse, and, contrary to some claims, emerging market central banks draw down reserves substantially. In effect emerging market central banks then release safe assets from their reserves, supplying safe havens to global investors.
Keywords: F02; E58; F3; G15; 330; capital flows; safe assets; international flow funds; vix; global liquidity; Öffentliche Anleihe; Währungsspekulation; Portfolio-Management; Institutioneller Investor; Wechselkurspolitik; Zentralbank; Welt